KLITIK DALAM BAHASA INGGRIS DAN BAHASA TOULOUR (SUATU ANALISIS KONTRASTIF) - PANGALILA, REVEN (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The title of this study is â€œKlitik dalam Bahasa Inggris dan Bahasa Toulour (Suatu Analisis Kontrastif)â€. The aims of this study is to identify, analyze, and describe the form and function of clitics in English and in Toulour Language, and to find out the similarities and differences ofÂ  clitics in both languages by using the theory of Zwicky (1994), Katamba (1994), and Whitman (1970). In this study, the English data were taken from several English books, and Toulour language data were taken from several informants by interviewing them. The method that has been applied in this study is contrastive analysis. The data of this sudy were analyzed descriptively then both languages were contrasted. The result shows that based on forms, English has 15 clitics which are divided into proclitics and enclitics. The function of these clitics are: auxiliary (Zwicky, 1970), adverb (Zwicky and Pullum, 1983), heads (Pullum, 1997), and pronomina (Radford, 1997). Toulour language has only 12 enclitics. The function of this clitics are: auxiliary and pronomina. In terms of similarity, both languages have enclitics, while based on function, both have the functions as auxiliary and pronomina. In terms of differences, based on forms clitics in English have both proclitics and enclitics while clitics in Toulour language have only enclitics. On the other hand, based on functions clitics in English have all four functions (auxiliary, adverb, heads, and pronomina), while clitics in Toulour language have only two functions as auxiliary and pronomina. Keywords : Clitic, English and Toulour Language, Contrastive Analysis.